Swimming skill and stroking characteristics of front crawl swimmers - Chatard, J. C.; Collomp, C.; Maglischo, E.; Maglischo, C. (International Journal of Sports Medicine, 1990)
The relationships between swimmers' biomechanical arm pulling pattern and technical ability were assessed in four "skilled" and five "less-skilled" athletes (the grouping being determined by a statistical method using all measures). The freestyle stroke was divided into five phases: entry (plus flight), downsweep, insweep, outsweep, and upsweep (round-out). VO2max, height, arm span, hydrostatic lift (maximum weight to maintain a balanced position under water), speed on a standardized 400 yd swim, and competition 500 yd time were measured. VO2max explained 64% of a 400 yd swim performed at 94% of 500 yd pace. Hydrostatic lift was the next most important structural variable. There was no significant difference between the two performance groups on any anthropometric, performance, or physiological variable. Biomechanical variables did differentiate the groups although there was great variation between individuals. Swimming mechanics were the primary factors differentiating the two groups. Even though the size of the groups was small, these variables were strong enough to overcome that deficiency. Implications : 1.Having a good aerobic capacity is the basic requirement for fast long-distance swimming performances. 2.The stroke pattern should emphasize the last part of the underwater stroke rather than the entry. 3.Gliding and excessive stretching under water after the entry should be minimized so that deceleration between individual arm cycles does not occur. 4.Swimming improvements are likely to be greater and more easily achieved through technique developments rather than through physiological and anthropometric factors.